Stability, Existence and Uniqueness of Boundary Value Problems for a Coupled System of Fractional Differential Equations - Al-Khateeb, Areen Saber Salah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The current thesis investigates four different nonlinear systems of fractional differential equations and deals with the existence, uniqueness, and stability of their solutions. The first studied problem is a coupled system of fractional differential equations with four-point integral boundary conditions. Existence and uniqueness of solutions are established by applying the contraction mapping principle and Leray–Schauder’s alternative theorem. Finding and results are demonstrated and supported with numerical examples. The second studied case is a boundary value problem for a coupled system of nonlinear fractional differential equations, where the existence and uniqueness of solutions is proven by using the Banach’s fixed point theorem and Schauder’s alternative. Furthermore, the Hyers-Ulam stability of solutions is discussed, sufficient stability conditions are drawn, and supporting numerical results are presented. In the third problem, a coupled system of Caputo type sequential fractional differential equations with integral boundary conditions is studied. Similarly, existence and uniqueness of solutions are discussed and established by employing contraction mapping principle and Leray–Schauder’s alternative theorem, and Hyers-Ulam stability of the boundary value problem is investigated. The last problem is a nonlinear Caputo type sequential fractional differential equation with non-separated non-local integral fractional boundary conditions. Existence, uniqueness, and Hyers-Ulam stability of solutions are discussed and established, and theoretical findings are presented and supported by numerical examples. Keywords: fractional differential equation, sequential, Caputo, integral boundary conditions, stability, Hyers-Ulam stability, existence and uniqueness of solutions.

ÖZ: Bu tezde, dört farklı doğrusal olmayan kesirli diferensiyel denklem sistemi araştırılmış ve çözümlerinin varlığı, benzersizliği ve kararlılığı çalışılmıştır. İlk çalışılan problem, dört noktalı integral sınır koşullarına sahip birleştirilmiş kesirli diferansiyel denklem sistemidir. Kasılma haritalama ilkesi ve Leray-Schauder’in alternatif teoremi uygulanarak çözümlerin varlığı ve benzersizliği sağlanmıştır. Elde edilen ve sonuçlar sayısal örneklerle gösterilmiş ve desteklenmiştir. İkinci çalışılan durum, Banach sabit nokta teoremi ve Schauder alternatifi kullanılarak çözümlerin varlığı ve benzersizliğinin kanıtlandığı birleştirilmiş doğrusal olmayan kesirli diferansiyel denklemler sistemi için bir sınır değer problemidir. Ayrıca, çözümlerin Hyers-Ulam kararlılığı tartışılmış, yeterli kararlılık koşulları verilmiş ve sayısal sonuçlar desteklenmiştir. Üçüncü problemde integral sınır koşullarına sahip eşleşmiş bir Caputo tipi ardışık kesirli diferansiyel denklem sistemi incelenmiştir. Benzer şekilde, daralma haritalama prensibi ve Leray-Schauder alternatif teoremi kullanılarak çözümlerin varlığı ve benzersizliği tartışılmış kurulmakta ve Sınır-Değer Probleminin Hyers-Ulam kararlılığı araştırılmıştır. Son problem, ayrılmamış lokal olmayan integral kesirli sınır koşullarıyla doğrusal olmayan bir Caputo tipi sıralı kesirli diferansiyel denklemdir. Çözümlerin varlığı, tekliği ve Hyers-Ulam kararlılığı tartışılmış ve sayısal örnekler ile elde edilen sonuçlar desteklenmiştir. Anahtar Kelimeler: kesirli diferansiyel denklem, sıralı, Caputo, integral sınır şartları, kararlılık, Hyers-Ulam kararlılığı, çözümlerin varlığı ve benzersizliği.
Doctor of Philosophy in Mathematics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2019. Supervisor: Prof. Dr. Nazim Mahmudov.
Keywords: Mathematics; Applied Mathematics and Computer Science; Boundary value problems--Differential equations; Fractional differential equation; sequential; Caputo; integral boundary conditions; stability; Hyers-Ulam stability; existence and uniqueness of solutions